Whole-genome screening in ankylosing spondylitis: evidence of non-MHC genetic-susceptibility loci. - Laval, S; Timms, A; Edwards, S; Bradbury, L; Brophy, S; Milicic, A; Rubin, L; Siminovitch, K; Weeks, D; Calin, A; Wordsworth, B; Brown, M (2001)
Ankylosing spondylitis (AS) is a common inflammatory arthritis predominantly affecting the axial skeleton. Susceptibility to the disease is thought to be oligogenic. To identify the genes involved, we have performed a genomewide scan in 185 families containing 255 affected sibling pairs. Two-point and multipoint nonparametric linkage analysis was performed. Regions were identified showing "suggestive" or stronger linkage with the disease on chromosomes 1p, 2q, 6p, 9q, 10q, 16q, and 19q. The MHC locus was identified as encoding the greatest component of susceptibility, with an overall LOD score of 15.6. The strongest non-MHC linkage lies on chromosome 16q (overall LOD score 4.7). These results strongly support the presence of non-MHC genetic-susceptibility factors in AS and point to their likely locations.